Microsoft encarta world atlas - Microsoft Corporation. (Microsoft, 1998)
A multimedia world atlas which includes images, music and sound clips. Spectacular 3-D virtual flights, 1.2 + million place names, 5000 + comprehensive articles, 9000 +internet links.